2020
DOI: 10.3389/fcell.2020.583234
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Enhance Adhesion and Osteogenic Differentiation of Initial Bone Marrow Stem Cells on Titanium Surfaces

Abstract: Successful osseointegration involves the biological behavior of bone marrow stem cells (BMSCs) on an implant surface; however, the role of BMSC-derived extracellular vesicles (EVs)/exosomes in osseointegration is little known. This study aimed to: (i) explore the interaction force between exosomes (Exo) and cells on a titanium surface; (ii) discuss whether the morphology and biological behavior of BMSCs are affected by exosomes; and (iii) preliminarily investigate the mechanism by which exosomes regulate cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Cell and animal experiments showed that this cell-free scaffold could efficiently regenerate bone tissue, which presents a novel bone regeneration method. Lan et al (88) reported a similar result further explained the mechanism that this osteogenic induction was achieved partly by activating the RhoA/ROCK signaling pathway.…”
Section: Coating Technologymentioning
confidence: 61%
“…Cell and animal experiments showed that this cell-free scaffold could efficiently regenerate bone tissue, which presents a novel bone regeneration method. Lan et al (88) reported a similar result further explained the mechanism that this osteogenic induction was achieved partly by activating the RhoA/ROCK signaling pathway.…”
Section: Coating Technologymentioning
confidence: 61%
“…It is, however, for OP and BSP. These results indicate that osteogenesis is not complete at 72 h. Lan et al demonstrated that the increase in ALP and OCN expression occurred only after 6 days of contact with a medium containing exosomes [62]. In their study, Jin et al observed an increase in ALP expression after 10 days of coculture with MSC-CM [60].…”
Section: Discussionmentioning
confidence: 93%
“…BMSC-EVs are useful in bone regeneration for overcoming issues such as inflammation, lower seeding efficiency, and immune response of cell transplantation, as well as enabling fast release and rapid concentration decay of growth factors [ 50 , 52 , 53 ]. Based on our previous findings [ 46 ], we further investigated the osteogenic capacity of EVs derived from Nell1 -modified BMSCs and determined how Nell1 -induced differentiation was coordinated with EV-miRNA changes. We isolated EVs from Nell1- modified BMSCs and demonstrated that modified EVs were able to induce BMSC osteogenesis in vitro and repaired bone defects in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that Nell1 modification could induce a series of changes in BMSCs as well as EVs. Based on the results of our previous study, which verified the osteo-inductive capacity of BMSC-EVs on the titanium surface of dental implants [ 46 ], we examined whether EVs secreted from Nell1 -modified BMSCs ( Nell1 /EVs) could induce osteogenesis in vitro and acellular bone regeneration in vivo ( Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%